Transcriptome of Salmonella enterica serovar Typhi within macrophages revealed through the selective capture of transcribed sequences - Faucher, Sébastien P. (National Academy of Sciences, 2006)
The cDNA obtained by selective capture of transcribed sequences is a complex mixture that can be used in conjunction with microarrays to determine global gene expression by a pathogen during infection. We used this method to study genes expressed by Salmonella enterica serovar Typhi, the etiological agent of typhoid fever, within human macrophages. Global expression profiles of Typhi grown in vitro and within macrophages at different time points were obtained and compared. Known virulence factors, such as the SPI-1- and SPI-2-encoded type III secretion systems, were found to be expressed as predicted during infection by Salmonella, which validated our data. Typhi inside macrophages showed increased expression of genes encoding resistance to antimicrobial peptides, used the glyoxylate bypass for fatty acid utilization, and did not induce the SOS response or the oxidative stress response. Genes coding for the flagellar apparatus, chemotaxis, and iron transport systems were down-regulated in vivo. Many cDNAs corresponding to genes with unknown functions were up-regulated inside human macrophages and will be important to consider for future studies to elucidate the intracellular lifestyle of this human-specific pathogen. Real-time quantitative PCR was consistent with the microarray results. The combined use of selective capture of transcribed sequences and microarrays is an effective way to determine the bacterial transcriptome in vivo and could be used to investigate transcriptional profiles of other bacterial pathogens without the need to recover many nanograms of bacterial mRNA from host and without increasing the multiplicity of infection beyond what is seen in nature.